PERANAN MAHASISWA KKN DALAM MEMAJUKAN UMKM DI ERA GLOBALISASI MELALUI PEMBUATAN WEBSITE, AKUN MEDIA SOSIAL PEMASARAN - Wijaya, Andika wisnu; kuniawan, tomi; Fauziah, Fauziah; juita, Wanda; awaliatun, Wiwid (Universitas Mataram, 2024)
The Community Service Program (KKN) in Lewirato Village, Bima City, West Nusa Tenggara, focuses on empowering Small and Medium Enterprises (SMEs) in the digital era. This research emphasizes enhancing the visibility and market reach of SMEs through digital marketing strategies, such as the use of social media, WhatsApp, Instagram, Facebook, and Twitter (X). This program is based on data showing that the use of digital applications such as Websites, WhatsApp, Instagram, Facebook, and TikTok has significantly increased in Indonesia. Therefore, utilizing digital platforms is crucial for SMEs to reach potential consumers. The methods used in this program include socialization, training, mentoring, and creating social media accounts. The results indicate increased sales, visibility, and knowledge about digitalization for SME operators. Challenges faced include limited internet access, difficulties in using technology, and lack of capital. Recommendations include expanding internet access, providing ongoing training programs, capital support, and developing digital infrastructure. This program is expected to serve as a model for other KKN programs in assisting SMEs to tackle challenges in the globalization era.